2016
DOI: 10.1002/nbm.3556
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gradient echo signal decays in healthy and cancerous prostate at 3T improves with a Gaussian augmentation of the mono-exponential (GAME) model

Abstract: A biomarker of cancer aggressiveness, such as hypoxia, could substantially impact treatment decisions in the prostate, especially radiation therapy, by balancing treatment morbidity (urinary incontinence, erectile dysfunction, etc.) against mortality. R2* mapping with Mono-Exponential (ME) decay modeling has shown potential for identifying areas of prostate cancer hypoxia at 1.5T. However, Gaussian deviations from ME decay have been observed in other tissues at 3T. The purpose of this study is to assess whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…As mentioned previously, it was recently reported that the microscopic frequency distribution in biological tissue is sometimes found to be more similar to Gaussian than to Lorentzian shape. 13,14 Based on this finding, one may ask whether there is a tendency to just one of these two distributions for each pixel, or whether a more generalized model allowing further distributions in between Gaussian and Lorentzian shape would be preferable. To examine this issue, it is beneficial to unify the different models (Lorentzian vs Gaussian distribution) in a new more general approach: For further analysis, three distribution types were considered: namely, the Lorentzian distribution, the Gaussian distribution, and the so-called "symmetric alphastable" distribution.…”
Section: Steidle and Schickmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, it was recently reported that the microscopic frequency distribution in biological tissue is sometimes found to be more similar to Gaussian than to Lorentzian shape. 13,14 Based on this finding, one may ask whether there is a tendency to just one of these two distributions for each pixel, or whether a more generalized model allowing further distributions in between Gaussian and Lorentzian shape would be preferable. To examine this issue, it is beneficial to unify the different models (Lorentzian vs Gaussian distribution) in a new more general approach: For further analysis, three distribution types were considered: namely, the Lorentzian distribution, the Gaussian distribution, and the so-called "symmetric alphastable" distribution.…”
Section: Steidle and Schickmentioning
confidence: 99%
“…[9][10][11][12] More recent works by Mulkern et al have shown clear deviations of the susceptibility-related signal decay from mono-exponential characteristics in brain 13 and prostate tissue. 14 It was demonstrated that those tissues often show a more Gaussian frequency distribution inside areas contributing to single pixels, reflecting a nearly Gaussian microscopic field distribution. The typical nearly Gaussian lineshape characteristics of signals in volumeselective spectra recorded in vivo support this assumption.…”
mentioning
confidence: 99%
“…Finally, a remark on our use of the Gaussian model rather than the Lorentzian to fit GESSE data, leading to reversible transverse relaxation rates being characterized by σ rather than R 2 ´: while we recognize that the assumption of a Lorentzian distribution of intra‐voxel precession frequencies (with width parameter R 2 ´) is likely to be more familiar to the reader, we note that, in addition to the data presented here, a number of recent studies have shown experimental support for the idea that this distribution is sometimes better modeled as a Gaussian (with width parameter σ ). These include studies of a variety of organs, such as brain, tooth, lung, prostate and uterus . It remains unclear, however, exactly when and why Gaussian rather than Lorentzian intra‐voxel frequency distributions might arise—a topic worthy of further investigation, whether by experiment or by theory …”
Section: Discussionmentioning
confidence: 99%
“…This model assumes that the intra‐voxel frequency distribution responsible for the reversible relaxation component is Gaussian rather than Lorentzian in shape, which is particularly relevant at higher field when this component becomes more prominent in T 2 * relaxation. It has been successfully used for T 2 * determinations from gradient‐echo measurements of human brain and prostate and gynecologic cancers at 3 T . In this study it was applied for the first time to estimate the T 2 * values of teeth and engineered tissue.…”
Section: Discussionmentioning
confidence: 99%
“…With the multi‐TE UTE data, the T 2 * values of fresh CPC, i.e. restored in human teeth and goat teeth at TP1, as well as the corresponding dental components (enamel and dentin), were estimated using the mono‐exponential (ME) model: sans-serif-italicS()TE=S00.25emsans-serifexp()TE/T2* and the GAME model: sans-serif-italicS()TE=S0sans-serif-italicexp()sans-serif-italicTE/T2sans-serif-italicexp()sans-serif-italicTEσ2/sans-serif2 where S 0 is the pseudo‐spin density and ~2.35 σ represents the full width at half‐maximum (FWHM) of the Gaussian frequency distribution responsible for the reversible transverse relaxation rate …”
Section: Methodsmentioning
confidence: 99%